Indonesia’s Economic Cooperation with BRICS: A Siyasah Maliyah Perspective - Aliyah Nur Alip; Beni Ahmad Saebani; Taufiq Alamsyah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The shift toward a multipolar global order has encouraged Indonesia to join BRICS as a full member to strengthen its strategic position and expand international economic cooperation. This study examines the strategic considerations behind Indonesia’s BRICS membership, its implications for national economic development, and its assessment from the perspective of siyāsah māliyah. This study contributes to the literature by analyzing Indonesia’s BRICS membership through the framework of siyāsah māliyah, which remains rarely discussed in previous studies. This study employs a normative legal research method with a descriptive-analytical approach based on library research. The findings indicate that Indonesia’s membership in BRICS is driven by the need to diversify economic partners, strengthen economic resilience, and expand access to development financing through the New Development Bank (NDB). BRICS membership potentially provides opportunities for financing strategic sectors such as infrastructure and renewable energy. However, the study also identifies risks, including economic dependence and geopolitical tensions. From the perspective of siyāsah māliyah, Indonesia’s cooperation with BRICS may be justified as long as it is directed toward al-maṣlaḥah al-‘āmmah, distributive justice, and economic welfare. Nevertheless, the benefits of such cooperation remain largely prospective, as no NDB-funded projects have yet been implemented in Indonesia.